Proposta de estratégias para climatização passiva para as salas de aula do Centro de Tecnologia da UFSM - Saad, Denise de Souza (2018)
In this work, passive strategies for air conditioning in the classrooms of the UFSM Technology Center were evaluated. In this work, the topic to be developed, the general and specific objectives, the justification and the work structure were presented. Afterwards, a review was made regarding the subject, describing the history of sustainability and the existing certifications, the panorama of the electric sector, the energy efficiency and the Procel Seal, besides addressing the computational simulation and the EnergyPlus program. In the methodology, it was initially determined the rooms that would be evaluated, room 236, located on the second floor and room 301, located on the third floor, under the critical conditions indicated by the norm NBR 15575(2013). Room 236 was evaluated for the winter period and the solution was the use of double glass miter. For room 301 were evaluated the use of ventilation, thermal insulation of the roof, roofing with metallic tile and sun protection. For room 236 the best result was the one that used double glazing, employing 3mm smooth colorless glass, with thermal transmittance of 2,731 W / m2K, without infiltration. For room 301, the best solution was the use of thermal insulation in the roof slab, with thermal transmittance of 0.621 W / m2K, ventilation of 15 air changes per hour and the use of solar protection on the west wall and metal roofing = 0.15. The energy consumption for the solutions was also evaluated, where the best solution for room 236 brought a reduction in energy consumption of 36% and for room 301 the reduction was of 22%. Another analysis was the fulfillment of the criterion of performance of NBR 15575 (2013) after passive strategies, room 236 performs superior performance and room 301 presents intermediate performance. At the end of the paper, the conclusions and proposals for future work were presented.